Trapping methodologies for functional canopy arthropod diversity in olive agroecosystem - Dimitrova A.; Livieratos I.; Gkisakis V. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
The value of a diverse and balanced community of canopy arthropods is undeniable in terms of pest management and overall agroecosystem functionality. However, a suitable monitoring methodology for them has not been well defined, especially in perennial crops. Field sampling conducted in Crete, Greece during autumn and spring was done in order to look into two types of trapping methodologies, yellow sticky traps (YST) and transparent sticky traps (TST) in organically managed olive orchard. The caught arthropods were organized in functional groups and compared on this basis. Although the differences between the diversity indices were not statistically significant, some differences came up between the total abundance and abundance of certain orders. The YSТ had a much higher abundance of arthropods while in absolute numbers, the TST present a more diverse and even canopy arthropod community. The agroecological approach seems to be useful and practical in terms of characterization of the properties of the YSТ and TST. Using the TST as a low cost, less labour demanding, replicable and easily set trapping methodology is suitable for estimation of the biodiversity of the canopy arthropods. This suggested that further research set on this approach can help in assessment and recommendation for further practices in perennial crops in order to reach a more stable and productive agroecosystem from ecological, social and economical aspect.
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)